Analyzing flow of funds in Iranian health care - Masaeli, Arashk; Basakha, Mehdi (Видавництво Львівської політехніки, 2011)
This paper first describes Iranian Health Care system, then counts the strengths and weakpoints if the system and finally analyzing flow of fund in Iranian Health Care system, highlights some of the areas which demandmore consideration.
Keywords: delivery system; finance; flow of funds; healthcare; social security